Heat Transfer Augmentation in Round Tube with Diamond-shaped Baffle Inserts - Khanoknaiyakarn, C.; Sripattanapipat, S.; Promvonge, P.; Skullong, S. (My University, 2019)
Influences of diamond-shaped baffle (DSB) insertion in a heat exchanger tube on its thermal performance are experimentally presented. The DSB elements were repeatedly mounted into the tube using two straight small rods to connect the DSBs together to produce the longitudinal vortex flows inside. The experiments were carried out in a constant surface heat-fluxed tube equiped with DSBs. The DSBs were placed periodically with an attack angle of 45° and a pitch spacing of three times of tube diameter (PR=P/D=3) while four different DSB heights called blockage ratios (BR=b/D=0.1, 0.2, 0.3 and 0.4) were offered. Air was used as the test fluid flowed into the tube to yield the Reynolds number (Re) in a range of 4190-26,000. The heat transfer rate and the pressure drop of the current work were presented in terms of Nusselt number (Nu) and friction factor (f), respectively. The experimental results showed that the DSB provides the increase in the heat transfer around 3.53-4.16 times higher than the smooth tube while friction factor increases around 16.68-29.52 times. To evaluate the gain of using the DSB, the thermal performance factor (TEF) is determined in a range of 1.25-1.55 whereas the highest TEF is found at BR=0.1.